Enzymatic Conversion of Sugar Beet Pulp: A Comparison of Simultaneous Saccharification and Fermentation and Separate Hydrolysis and Fermentation for Lactic Acid Production - Joanna Berlowska; Weronika Cieciura-Włoch; Halina Kalinowska; Dorota Kregiel; Sebastian Borowski; Ewelina Pawlikowska; Michał Binczarski; Izabela Witonska (Food Technology and Biotechnology, 2018)
This study compares the efficiency of lactic acid production by separate hydrolysis and fermentation (SHF) or simultaneous saccharification and fermentation (SSF) of sugar beet pulp, a byproduct of industrial sugar production. In experiments, sugar beet pulp was hydrolyzed using five commercial enzymes. A series of shake flask fermentations were conducted using five selected strains of lactic acid bacteria (LAB). The differences in the activities of the enzymes for degrading the principal sugar beet pulp components were reflected in the different yields of total reducing sugars. The highest yields after hydrolysis and the lowest quantities of insoluble residues were obtained using a mixture (1:1) of Viscozyme® and Ultraflo® Max. In the SHF process, only a portion of the soluble sugars released by the enzymes from the sugar beet pulp was assimilated by the LAB strains. In SSF, low enzyme loads led to reduction in the efficiency of sugar accumulation. The risk of carbon catabolic repression was reduced. Our results suggest that SSF has advantages over SHF, including lower processing costs and higher productivity. Lactic acid yield in SSF mode (approx. 30 g/L) was 80–90 % higher than that in SHF.